2009
DOI: 10.1038/ejcn.2009.54
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of women who frequently under report their energy intake: a doubly labelled water study

Abstract: Background/Objectives: We applied three dietary assessment methods and aimed at obtaining a set of physical, social and psychological variables that can discriminate those individuals who did not underreport ('never under-reporters'), those who underreported in one dietary assessment method ('occasional under-reporters') and those who underreported in two or three dietary assessment methods ('frequent under-reporters'). Participants/Methods: Sixty-five women aged 18-57 years were recruited for this study. Tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
73
3
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 35 publications
6
73
3
2
Order By: Relevance
“…Doubly labelled water studies indicate that women are more prone to under-reporting energy than men (Hebert et al, 1995(Hebert et al, , 1997. There is also evidence that energy reporting accuracy among women varies according to social desirability, adiposity and education level (Hebert et al, 1995(Hebert et al, , 1997(Hebert et al, , 2001Scagliusi et al, 2009). Therefore, the lack of evidence for significant differences between associations estimated using the FFQ and 7DD among women in this study may reflect a consistency of reporting error that extends across both instruments.…”
Section: Discussioncontrasting
confidence: 52%
“…Doubly labelled water studies indicate that women are more prone to under-reporting energy than men (Hebert et al, 1995(Hebert et al, , 1997. There is also evidence that energy reporting accuracy among women varies according to social desirability, adiposity and education level (Hebert et al, 1995(Hebert et al, , 1997(Hebert et al, , 2001Scagliusi et al, 2009). Therefore, the lack of evidence for significant differences between associations estimated using the FFQ and 7DD among women in this study may reflect a consistency of reporting error that extends across both instruments.…”
Section: Discussioncontrasting
confidence: 52%
“…We did not conduct dietary surveys on participants. Previous studies reported that obese women tended to under-report their food intake (17,18) , and folate from naturally occurring food sources exhibits variable and incomplete bioavailability, which can be affected by physiological conditions, pharmaceuticals and genetic polymorphisms (19)(20)(21) . Third, BMI was measured in early pregnancy (95 % were measured before 15 weeks) and this may lead to misclassification of obesity, although the weight gain in early second trimester is generally small (22) .…”
Section: Discussionmentioning
confidence: 99%
“…Várias características têm sido associadas ao sub-relato em diversos trabalhos, dentre as quais se destacam: sexo, idade, condições socioeconô-micas e índice de massa corporal (IMC) 6,7,8,9,10 .…”
Section: Introductionunclassified